THE EFFECT OF INNOVATION ON COMPANY PERFORMANCE WITH OWNERSHIP CONCENTRATION AS A MODERATING VARIABLE - Faturachman, Dedy (Jurnal Akuntansi dan Keuangan Indonesia, 2023)
An open economy and a supportive environment encourage researchers to research this phenomenon. This study aims to provide empirical evidence regarding the effect of innovation on firm performance and the moderating role of ownership concentration. This research is quantitative research with an associative explanatory approach. The sample used is 821 observational data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. The analysis technique used is multiple regression analysis and moderate regression analysis. The study results show that innovation positively affects company performance; the concentration of ownership in the concentrated ownership strengthens the effect of innovation on company performance.